Mitigation Measures for Windfarm Effects on Radar Systems - Omar Abu Ella; Khawla A. Alnajjar (International Journal of Aerospace Engineering)
Windfarms can have a significant impact on radar systems, especially air surveillance radar. This is because it is usually designed to show only moving targets and cancel out stationary objects. However, the rotation of wind turbine blades can be detected by radar as a false flight or target. Clutter or interference caused by windfarms can reduce radar sensitivity in critical regions, making real targets disappear. This could in turn affect the deployment of windfarms and lead to the cancellation of future renewable energy projects and plans. This paper presents the different strategies and techniques used to mitigate the windfarm impact on radar systems. Precisely, we aim throughout this article to classify the main currently adopted approaches, view the recent trends and research directions in this field, and try to trace the advantages and drawbacks along with the challenges of deploying such schemes.